Self-Efficacy with Achievement Motivation in Students Working VIII Semester Faculty of Economics and Business, Faculty of Engineering and Faculty of Teacher Training and Education at Muhammadiyah University, Sidoarjo: Efikasi Diri dengan Motivasi Berprestasi pada Mahasiswa Bekerja Semester VIII Fakultas Ekonomi dan Bisnis, Fakultas Teknik dan Fakultas Keguruan dan Ilmu Pendidikan di Universitas Muhammadiyah Sidoarjo - Dewi, Ananda Putri Aisyah; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the relationship between self-efficacy and achievement motivation and how much influence self-efficacy on achievement motivation on eighth semester student students at the Faculty of Economics and Business, Faculty of Engineering and Faculty of Teacher Training and Education Sciences at Muhammadiyah University Sidoarjo. This research was conducted with a quantitative correlational research method, using simple random sampling with a sample of 227 students. The measuring instrument uses two scales, self-efficacy scale and achievement motivation scale with Pearson product moment correlation technique with the help of IBM Statistics 20 Version for Windows. The results of the analysis show that there is a relationship between self-efficacy and achievement motivation. The implications of this study is to develop student achievement and provide interventions to improve the quality of education. Maximum improvement of education qualification can improve self-efficacy and achievement motivation in working students